2021
DOI: 10.31584/jhsmr.2021828
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Outcomes of Mortality among Extremely Preterm Infants From a Tertiary Hospital in Thailand: 15-Year Experience

Abstract: Objective: It remains unclear if changes in neonatal care have resulted in better outcomes for extremely preterm infants (EPTs). This study was to evaluate neonatal mortality and morbidity in EPTs.Material and Methods: A retrospective cohort study of EPTs at a gestational age (GA) ≤28 weeks, who were admitted to the neonatal intensive care unit between January 2004 and December 2018. The study was divided into 2 periods, from 2004-2010 and 2011-2018. The likelihood ratio test in Multiple Cox regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…In our study, 43 (28.5%) and 86 (57.0%) extremely preterm neonates died and had composite outcomes, respectively. The mortality rate from this study (2014-2021) was lower than the previous period (2004-2018, 66/188, 35.1%) in the same unit 16 ; however, it was still higher than in studies from the iNeo network (13.5%;…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In our study, 43 (28.5%) and 86 (57.0%) extremely preterm neonates died and had composite outcomes, respectively. The mortality rate from this study (2014-2021) was lower than the previous period (2004-2018, 66/188, 35.1%) in the same unit 16 ; however, it was still higher than in studies from the iNeo network (13.5%;…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies have reported several risk factors associated with an increased risk of mortality or morbidities in very preterm infants, e.g., lower gestational age (GA) and small for GA (SGA). [11][12][13][14][15][16] However, there are few studies which have examined risk factors for composite outcomes (mortality and/or morbidities) in middle-or low-income countries. If the modifiable risk factors could be identified, perhaps the rates could be decreased especially in resourcelimited settings.…”
Section: Introductionmentioning
confidence: 99%